2019
DOI: 10.3791/59258
|View full text |Cite
|
Sign up to set email alerts
|

Forced Flowering in Mandarin Trees under Phytotron Conditions

Abstract: Phytotron has been widely used to assess the effect of numerous parameters on the development of many species. However, less information is available on how to achieve fast profuse flowering in young fruit trees with this plant growth chamber. This study aimed to outline the design and performance of a fast clear methodology to force flowering in young mandarin trees (cv. Nova and cv. Clemenules) and to analyze the influence of induction intensity on inflorescence type. The combination of a short water stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Finally, the vast majority of experiments run on floral induction have shown that exogenous GA applications during the induction period reduce the quantity of flowers [8590]. If we take into account that flowering is usually induced through stresses, such as low temperatures [91,92] or water stress [93], once again it would seem that GA has an antagonistic effect on stress hormones like ABA. In all cases, the induction response was proportional to the amount of stress [93].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, the vast majority of experiments run on floral induction have shown that exogenous GA applications during the induction period reduce the quantity of flowers [8590]. If we take into account that flowering is usually induced through stresses, such as low temperatures [91,92] or water stress [93], once again it would seem that GA has an antagonistic effect on stress hormones like ABA. In all cases, the induction response was proportional to the amount of stress [93].…”
Section: Discussionmentioning
confidence: 99%
“…If we take into account that flowering is usually induced through stresses, such as low temperatures [91,92] or water stress [93], once again it would seem that GA has an antagonistic effect on stress hormones like ABA. In all cases, the induction response was proportional to the amount of stress [93]. Therefore, GA lowers the floral induction level, probably by counteracting stress hormones.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations